Secondary battery and electric device

By setting up a multi-layer active material layer on the positive electrode current collector surface of the lithium iron phosphate battery and introducing titanium and boron, the problems of air bloating, interface deterioration and capacity attenuation in the high-temperature storage process are solved, and excellent high-temperature storage performance and energy density are achieved.

CN119786533AActive Publication Date: 2025-04-08SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411989260.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

During the high-temperature storage process, lithium iron phosphate batteries are prone to problems such as gas bloating, interface deterioration and rapid capacity decay.

Method used

By providing the first positive electrode active material layer and the second positive electrode active material layer on the surface of the positive electrode current collector, defining the molar ratio difference between the lithium element and the phosphorus element, and introducing titanium and boron to form a protected fast ion conductor coating, the kinetics and structural stability of the positive electrode sheet are improved.

Benefits of technology

It effectively solves the electrode polarization problem accumulated by the battery during the high-temperature storage process, improves the storage performance of the battery, and improves the high-temperature storage capacity retention rate and DCR growth rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223559310000161
    Figure BDA0005223559310000161
  • Figure BDA0005223559310000171
    Figure BDA0005223559310000171
Patent Text Reader

Abstract

The invention discloses a secondary battery and an electric device, and belongs to the technical field of batteries. According to the secondary battery provided by the invention, the first positive electrode active material layer is arranged on at least one surface of the positive electrode current collector, and the second positive electrode active material layer is arranged on the surface of the first positive electrode active material layer; the molar ratio P1 of the lithium element to the phosphorus element in the first positive electrode active material layer is limited to be smaller than the molar ratio P2 of the lithium element to the phosphorus element in the second positive electrode active material layer; the first lithium iron phosphate compound and the second lithium iron phosphate respectively and independently comprise titanium and / or boron; meanwhile, the first positive electrode active material layer is limited to comprise titanium aluminum phosphate; therefore, gas generation swelling and interface deterioration of the battery in the storage process can be effectively improved, and the high-temperature storage capacity retention rate of the battery is improved on the basis of ensuring the energy density of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and in particular relates to a secondary battery and an electrical device. Background Art

[0002] Lithium iron phosphate batteries, in which the viscosity of the electrolyte at 25°C is ≤3.0mPa.s, are prone to battery gas bulging, interface deterioration, and rapid capacity decay during high-temperature storage at 60°C 100% SOC. Through the analysis and disassembly of lithium iron phosphate storage batteries, it is generally easy to experience battery gas bulging and purple spot interfaces during 300-400 days of storage. At present, the main way to solve the above problems is to optimize the content of lithium iron phosphate modifying elements to improve the structural stability of the positive electrode, reduce the compaction density of the negative electrode to improve the kinetic performance of the negative electrode, and optimize the electrolyte formula, but it affects the battery cost, energy density, and verification cycle. With the increase of storage days, the side reaction products of the positive and negative electrode surfaces and the electrolyte gradually increase, and the positive and negative electrode interfaces and mass transfer impedances increase rapidly. Finally, the overpotential on both sides of the positive and negative electrode sheets gradually increases, and the gas production gradually increases, resulting in a significant decrease in the storage performance of the battery. Summary of the invention

[0003] The purpose of the present application is to solve the technical problems in the prior art that when the viscosity of the electrolyte at 25°C is ≤3.0mPa.s, the capacity of the secondary battery decays significantly and the battery produces gas and swells during high-temperature storage at 60°C / 100% SOC, and to provide a secondary battery and electrical device with excellent storage performance and high energy density under high-temperature conditions (60°C).

[0004] One embodiment of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes a positive electrode current collector and a first positive electrode active material layer and a second positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the first positive electrode active material layer is disposed between the positive electrode current collector and the second positive electrode active material layer;

[0005] The first positive electrode active material layer includes a first lithium iron phosphate compound and aluminum titanium phosphate, and the second positive electrode active material layer includes a second lithium iron phosphate compound;

[0006] The first lithium iron phosphate compound and the second lithium iron phosphate each independently include a first element;

[0007] The first element includes titanium and / or boron;

[0008] The molar ratio P1 of lithium to phosphorus in the first positive electrode active material layer is less than the molar ratio P2 of lithium to phosphorus in the second positive electrode active material layer;

[0009] The mass percentage W1 of the first element in the first lithium iron phosphate compound is less than the mass percentage W2 of the first element in the second lithium iron phosphate compound;

[0010] The viscosity of the electrolyte at 25° C. is ≤3.0 mPa.s.

[0011] As an embodiment of the present application, in the first positive electrode active material layer, the mass percentage of the aluminum titanium phosphate is 0.2-1.0%.

[0012] As an implementation scheme of the present application, 0.01≤P2-P1≤0.06.

[0013] As an embodiment of the present application, the 500ppm≤W2-W1≤1500ppm.

[0014] As an embodiment of the present application, the first element includes titanium and boron;

[0015] The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is less than the mass percentage Ti2 of titanium in the second lithium iron phosphate compound;

[0016] The mass percentage B1 of boron in the first lithium iron phosphate compound is less than the mass percentage B2 of boron in the second lithium iron phosphate compound.

[0017] As an embodiment of the present application, the 400ppm≤Ti2-Ti1≤1000ppm.

[0018] As an embodiment of the present application, the 100 ppm≤B2-B1≤500 ppm.

[0019] As an embodiment of the present application, a molar ratio P1 of lithium element to phosphorus element in the first positive electrode active material layer is 1.00 to 1.05.

[0020] As an embodiment of the present application, a molar ratio P2 of lithium element to phosphorus element in the second positive electrode active material layer is 1.01 to 1.11.

[0021] As an embodiment of the present application, the mass percentage Ti1 of titanium in the first lithium iron phosphate compound is 200 to 5000 ppm.

[0022] As an embodiment of the present application, the mass percentage Ti2 of titanium in the second lithium iron phosphate compound is 600 to 6000 ppm.

[0023] As an embodiment of the present application, the mass percentage B1 of boron in the first lithium iron phosphate compound is 100 to 1000 ppm.

[0024] As an embodiment of the present application, the mass percentage B2 of boron in the second lithium iron phosphate compound is 200 to 1500 ppm.

[0025] As an embodiment of the present application, the single-side thickness of the first positive electrode active material layer is 10 to 60 μm.

[0026] As an embodiment of the present application, the thickness of the second positive electrode active material layer is 10 to 60 μm.

[0027] As an embodiment of the present application, the thickness expansion rate of the first positive electrode active material layer is 3.4% to 4.3%.

[0028] As an embodiment of the present application, the thickness expansion rate of the second positive electrode active material layer is 3.4% to 5.4%.

[0029] Another embodiment of the present application provides an electric device, comprising the secondary battery described in the present application.

[0030] The beneficial effects of this application are:

[0031] The secondary battery provided by the present application comprises a first positive electrode active material layer on at least one surface of a positive electrode current collector, and a second positive electrode active material layer arranged on the surface of the first positive electrode active material layer and away from the positive electrode current collector, and the molar ratio of lithium element to phosphorus element in the first positive electrode active material layer is limited to P1 less than the molar ratio of lithium element to phosphorus element in the second positive electrode active material layer P2, and the first lithium iron phosphate compound and the second lithium iron phosphate each independently include titanium and / or boron, and it is also limited that the first positive electrode active material layer includes titanium aluminum phosphate; thereby effectively solving the problem of electrode polarization accumulated during high-temperature storage of the battery at 60°C caused by the viscosity of the electrolyte at 25°C being ≤3.0mPa.s, and effectively improving the gas production bulging and interface deterioration of the battery during storage, thereby improving the high-temperature storage capacity retention rate of the battery on the basis of ensuring the battery energy density, and improving the DCR growth rate of the battery, that is, having excellent high-temperature storage performance. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific embodiments.

[0033] Unless otherwise specified, the reagents, methods and equipment used in this application are conventional reagents, methods and equipment in the art.

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] In one embodiment of the present application, the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes a positive electrode current collector and a first positive electrode active material layer and a second positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the first positive electrode active material layer is disposed between the positive electrode current collector and the second positive electrode active material layer;

[0038] The first positive electrode active material layer includes a first lithium iron phosphate compound and aluminum titanium phosphate, and the second positive electrode active material layer includes a second lithium iron phosphate compound;

[0039] The first lithium iron phosphate compound and the second lithium iron phosphate each independently include a first element;

[0040] The first element includes titanium and / or boron;

[0041] The molar ratio P1 of lithium to phosphorus in the first positive electrode active material layer is less than the molar ratio P2 of lithium to phosphorus in the second positive electrode active material layer;

[0042] The mass percentage W1 of the first element in the first lithium iron phosphate compound is less than the mass percentage W2 of the first element in the second lithium iron phosphate compound;

[0043] The viscosity of the electrolyte at 25° C. is ≤3.0 mPa.s.

[0044] The secondary battery provided by the present application comprises a first positive electrode active material layer on at least one surface of a positive electrode current collector, and a second positive electrode active material layer arranged on the surface of the first positive electrode active material layer and away from the positive electrode current collector, and the molar ratio of lithium element to phosphorus element in the first positive electrode active material layer is limited to P1 less than the molar ratio of lithium element to phosphorus element in the second positive electrode active material layer P2, and the first lithium iron phosphate compound and the second lithium iron phosphate each independently include titanium and / or boron, and the first positive electrode active material layer is further limited to include titanium aluminum phosphate; thereby, the electrode polarization accumulated during high-temperature storage at 60°C caused by the viscosity of the electrolyte at 25°C being ≤3.0mPa.s can be effectively solved, and the gas production bulging and interface deterioration of the battery during storage can be effectively improved, thereby improving the high-temperature storage capacity retention rate of the battery and improving the DCR growth rate of the battery on the basis of ensuring the energy density of the battery, that is, having excellent high-temperature storage performance.

[0045] Specifically, in the first aspect, the molar ratio P1 of lithium and phosphorus in the first positive electrode active material layer is less than the molar ratio P2 of lithium and phosphorus in the second positive electrode active material layer, and the first positive electrode active material layer includes titanium aluminum phosphate, which can effectively form a protected fast ion conductor coating in the first positive electrode active material layer, and can also effectively improve the positive electrode plate dynamics, reduce the damage to the structure of the positive electrode active material layer caused by overpotential during storage and the increase in SEI interface and phase transfer impedance caused by interface side reactions; in addition, the second positive electrode active material layer can effectively improve the wettability, dynamics and structural stability of the positive electrode plate, and can also reduce the side reactions between the surface of the positive electrode plate and the electrolyte and the growth of SEI interface and phase transfer impedance and the increase in diffusion impedance between the negative electrode, which greatly improves the purple spot interface risk of the negative electrode; at the same time, the second positive electrode active material layer can inhibit the dissolution of Fe element and the generation of electrolyte gas in lithium iron phosphate during long-term high-temperature storage, which greatly improves the battery's 60°C high-temperature storage capacity retention rate and DCR growth rate. Secondly, the introduction of titanium and / or boron as the first element and satisfying a specific mass percentage relationship can effectively increase the interlayer spacing of lithium iron phosphate, as well as the structural stability and conductivity of lithium iron phosphate, increase energy density, and also better improve the high-temperature storage performance of the battery.

[0046] It should be noted that the method for testing and calculating the molar ratio of lithium and phosphorus in the first positive electrode active material layer and the second positive electrode active material includes the following steps: using ICP to test the content of lithium and phosphorus in different coating powders respectively, and then converting them into molar ratios.

[0047] It should be noted that the testing method for the mass percentage of the first element in the first lithium iron phosphate compound and the second lithium iron phosphate compound includes the following steps: using ICP to test the molar content of the first element in different coating powders, respectively, and then converting it into the mass and mass fraction of the first element, the mass percentage of the first element in the lithium iron phosphate compound = the mass of the first element in the lithium iron phosphate compound / the mass of the lithium iron phosphate compound.

[0048] It should be noted that if the first element of the first lithium iron phosphate compound in the first positive electrode active material layer contains titanium, the aluminum content in the first positive electrode active material layer powder is first tested by ICP, and then converted into titanium content based on aluminum titanium phosphate. Subsequently, the total molar content of titanium in the first positive electrode material layer powder obtained by ICP test is subtracted from the molar content of titanium in the converted aluminum titanium phosphate to obtain the molar content of titanium in the first lithium iron phosphate compound, and then its mass percentage in the first lithium iron phosphate compound is calculated.

[0049] It should be noted that the method for testing the viscosity of the electrolyte at 25° C. includes the following steps: taking a certain amount of electrolyte sample and passing it through a viscometer to test the viscosity at room temperature.

[0050] In one embodiment, the viscosity of the electrolyte at 25° C. is 1.2-2.8 mPa.s.

[0051] Exemplarily, the viscosity of the electrolyte at 25°C may be any point value or any two point range values ​​between 1.2 and 2.8 mPa.s, for example, it may be one of 1.2 mPa.s, 1.5 mPa.s, 1.8 mPa.s, 2.0 mPa.s, 2.2 mPa.s, 2.4 mPa.s, 2.6 mPa.s, 2.8 mPa.s or any two range values.

[0052] In one embodiment, in the first positive electrode active material layer, the mass percentage of the aluminum titanium phosphate is 0.2-1.0%.

[0053] It should be noted that the test method for the mass percentage of aluminum titanium phosphate in the first positive electrode active material layer is: use ICP to test the content of aluminum element in the first coating powder, convert it into the molar ratio of aluminum titanium phosphate, and then convert it into the mass percentage of aluminum titanium phosphate.

[0054] Exemplarily, in the first positive electrode active material layer, the mass percentage of aluminum titanium phosphate can be any point value or any two point range values ​​between 0.2 and 1.0%, for example, it can be one of 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two range values.

[0055] The present application study found that the introduction of aluminum titanium phosphate can effectively form a fast ion channel in the first positive electrode active material layer, thereby effectively reducing the structural damage to the first positive electrode active material layer caused by overpotential and the increase in CEI interface and phase transfer impedance caused by interfacial side reactions; especially when the mass percentage of aluminum titanium phosphate is further selected to be 0.2-1.0%, the obtained battery has better high-temperature storage performance and higher energy density.

[0056] In one embodiment, 0.01≤P2-P1≤0.06.

[0057] Exemplarily, P2-P1 may be any point value or any two point range values ​​between 0.01 and 0.06, for example, it may be one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06 or any two range values.

[0058] The research in this application found that when the difference between the molar ratio P2 of lithium and phosphorus in the second positive electrode active material layer and the molar ratio P1 of lithium and phosphorus in the first positive electrode active material layer is further selected to be between 0.01 and 0.06, it can better improve the structural stability of the positive electrode plate, reduce side reactions and battery polarization during high-temperature storage, improve the risk of purple spot interface of the negative electrode, and inhibit the dissolution of iron elements and the occurrence of electrolyte gas production during the storage process; thereby effectively improving the storage performance of the secondary battery at high temperature.

[0059] In one embodiment, the 500 ppm≤W2-W1≤1500 ppm.

[0060] Exemplarily, the W2-W1 may be any point value or any two point range values ​​between 500 and 1500 ppm, for example, it may be one of 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm or any two range values.

[0061] The present application study found that when the difference between the mass percentage W2 of the first element in the second lithium iron phosphate compound and the mass percentage W1 of the first element in the first lithium iron phosphate compound is 500-1500 ppm, the structural stability of the positive electrode plate can be better improved, and the high temperature storage performance of the secondary battery can be improved.

[0062] In one embodiment, the first element includes titanium and boron;

[0063] The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is less than the mass percentage Ti2 of titanium in the second lithium iron phosphate compound;

[0064] The mass percentage B1 of boron in the first lithium iron phosphate compound is less than the mass percentage B2 of boron in the second lithium iron phosphate compound.

[0065] The present application has found that when the first elements of the first lithium iron phosphate compound and the second lithium iron phosphate compound both include titanium and boron, and the mass percentages of titanium and boron in the first lithium iron phosphate compound and the second lithium iron phosphate compound satisfy the relationship of the present application, it is possible to increase the interlayer spacing of the lithium iron phosphate while improving the structural stability and electrical conductivity of the lithium iron phosphate, improve the kinetics of the lithium iron phosphate and the lithium precipitation phenomenon of the positive electrode, thereby effectively improving the high-temperature storage performance of the secondary battery.

[0066] In one embodiment, the 400ppm≤Ti2-Ti1≤1000ppm.

[0067] Exemplarily, the Ti2-Ti1 may be any point value or any two point range values ​​between 400 and 1000 ppm, for example, it may be one or any two range values ​​of 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm.

[0068] In one embodiment, the 100 ppm≤B2-B1≤500 ppm.

[0069] Exemplarily, the B2-B1 may be any point value or any two point range values ​​between 100 and 500 ppm, for example, it may be one or any two range values ​​of 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm.

[0070] The present application has found that when the first elements of the first lithium iron phosphate compound and the second lithium iron phosphate compound both include titanium and boron, and the difference in mass percentage of titanium and boron in the first lithium iron phosphate compound and the second lithium iron phosphate compound is within the above range, the comprehensive performance of the secondary battery obtained is better.

[0071] In one embodiment, the molar ratio P1 of lithium element to phosphorus element in the first positive electrode active material layer is 1.00-1.05.

[0072] For example, the molar ratio P1 of lithium to phosphorus in the first positive electrode active material layer may be any point value or any two point range values ​​between 1.00 and 1.05, for example, one of 1.00, 1.01, 1.02, 1.03, 1.04, 1.05 or any two range values.

[0073] In one embodiment, the molar ratio P2 of lithium element to phosphorus element in the second positive electrode active material layer is 1.01-1.11.

[0074] Exemplarily, the molar ratio P2 of lithium element to phosphorus element in the second positive electrode active material layer may be any point value or any two point range values ​​between 1.01 and 1.11, for example, it may be one of 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11 or any two range values.

[0075] The present application has found that when the molar ratio P1 of lithium to phosphorus in the first positive electrode active material layer and the molar ratio P2 of lithium to phosphorus in the second positive electrode active material layer are within the above range, the difference between P2-P1 is more conducive to the difference in gram capacity and N / P ratio between the overall inner active coating and the surface active coating lithium iron phosphate, surface structure stability and impedance growth, and in particular can improve the side reactions and gas production between the surface lithium iron phosphate coating and the electrolyte.

[0076] In one embodiment, the mass percentage Ti1 of titanium in the first lithium iron phosphate compound is 200-5000 ppm.

[0077] Exemplarily, the mass percentage Ti1 of titanium in the first lithium iron phosphate compound may be any point value or any two point range values ​​between 200 and 5000 ppm, for example, it may be one of 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm or any two range values.

[0078] In one embodiment, the mass percentage Ti2 of titanium in the second lithium iron phosphate compound is 600-6000 ppm.

[0079] Exemplarily, the mass percentage Ti2 of titanium in the second lithium iron phosphate compound can be any point value between 600 and 6000 ppm or any two point range values, for example, it can be one of 600 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, 5500 ppm, 6000 ppm or any two range values.

[0080] In one embodiment, the mass percentage B1 of boron in the first lithium iron phosphate compound is 100-1000 ppm.

[0081] Exemplarily, the mass percentage B1 of boron in the first lithium iron phosphate compound can be any point value or any two point range values ​​between 100 and 1000 ppm, for example, it can be one of 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm or any two range values.

[0082] In one embodiment, the mass percentage B2 of boron in the second lithium iron phosphate compound is 200-1500 ppm.

[0083] Exemplarily, the mass percentage B2 of boron in the second lithium iron phosphate compound can be any point value or any two point range values ​​between 200 and 1500 ppm, for example, it can be one of 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1500 ppm or any two range values.

[0084] The present application study found that when the mass percentages of titanium and boron in the first lithium iron phosphate compound and the second lithium iron phosphate compound are respectively within the above ranges, the difference of W2-W1 is more conducive to the kinetic difference and surface structural stability and impedance growth of the overall inner active coating and the surface active coating lithium iron phosphate, and in particular can improve the side reactions and gas production between the surface lithium iron phosphate coating and the electrolyte.

[0085] In one embodiment, the single-side thickness of the first positive electrode active material layer is 10-60 μm.

[0086] It should be noted that the test method for the single-side thickness of the first positive electrode active material layer is: dimensional calibration by CP+SEM (Cross Section Polisher-Scanning Electron Microscope).

[0087] Exemplarily, the single-sided thickness of the first positive electrode active material layer may be any point value or any two point range values ​​between 10 and 60 μm, for example, it may be one of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm or any two range values.

[0088] In one embodiment, the thickness of the second positive electrode active material layer is 10-60 μm.

[0089] It should be noted that the thickness of the second positive electrode active material layer is tested by CP+SEM size calibration.

[0090] Exemplarily, the thickness of the second positive electrode active material layer may be any point value or any two point range values ​​between 10 and 60 μm, for example, it may be one of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm or any two range values.

[0091] The research in this application found that when the single-sided thickness of the first positive electrode active material layer and the thickness of the second positive electrode active material layer are further selected within the above range, the double-coated lithium iron phosphate battery has better storage performance at 60°C; if the coating is too thin, the uniformity is poor, and the equipment capacity is difficult to meet. If it is too thick, the negative electrode is more likely to have a lithium plating interface when it is fully charged.

[0092] In one embodiment, the thickness expansion rate of the first positive electrode active material layer is 3.4% to 4.3%.

[0093] In one embodiment, the thickness expansion rate of the second positive electrode active material layer is 3.4% to 5.4%.

[0094] It should be noted that the thickness expansion rate of the active material layer refers to the change rate of the thickness of the active material layer under different storage days.

[0095] The specific calculation formula is:

[0096] The expansion rate of the active material layer stored for N days = (thickness of the active material layer stored for N days - thickness of the active material layer before storage) / thickness of the active material layer before storage × 100%;

[0097] Wherein: the thickness of the active material layer stored for N days refers to the thickness of the active material layer obtained by CP+SEM calibration after storage for N days; the thickness of the active material layer before storage refers to the thickness of the active material layer obtained by CP+SEM calibration before storage.

[0098] Exemplarily, the battery thickness expansion rate caused by the first positive electrode active material layer is any point value or any two point range values ​​between 3.4% and 4.3%, for example, it can be one of 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.3% or any two range values, and the battery thickness expansion rate caused by the second positive electrode active material layer is any point value or any two point range values ​​between 3.4% and 5.4%, for example, it can be one of 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4% or any two range values.

[0099] The present application has found that when the thickness expansion ratio of the first positive electrode active material layer and the second positive electrode active material layer is within the above range, the energy density and storage performance of the battery are slightly better.

[0100] In one embodiment, the first positive electrode active material layer and the second positive electrode active material layer further include a conductive agent and a positive electrode binder. The present application has no limitation on the conductive agent and the positive electrode binder, and any known conductive agent and positive electrode binder can be used.

[0101] Exemplarily, the conductive agent includes conductive graphite; and the positive electrode binder includes polyvinylidene fluoride.

[0102] In one embodiment, the positive electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of electrical conduction and current collection. In one embodiment, the positive electrode current collector may be made of a metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector is made of aluminum foil or carbon-coated aluminum foil.

[0103] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material. The present application has no limitation on the negative electrode active material, and any known negative electrode active material can be used. As an example, the negative electrode active material can be at least one of artificial graphite, natural graphite, silicon-carbon composite material, silicon alone, silicon oxide, and hard carbon.

[0104] In one embodiment, the negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of conducting electricity and collecting current. In one embodiment, the negative electrode current collector may be made of a metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector is made of copper foil.

[0105] In one embodiment, the electrolyte further comprises an organic solvent and a lithium salt. The present application has no limitation on the organic solvent and the lithium salt in the electrolyte, and any known organic solvent and lithium salt can be used.

[0106] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0107] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.

[0108] In one embodiment of the present application, the present application proposes an electrical device, and the electrical device includes the secondary battery described in the present application.

[0109] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0110] Example 1

[0111] The present invention provides a secondary battery, wherein a method for preparing the secondary battery comprises the following steps:

[0112] (1) Preparation of positive electrode sheet

[0113] S1, mixing a first lithium iron phosphate compound (a molar ratio of lithium element to phosphorus element P1 is 1.02, a mass percentage of titanium Ti1 is 1000 ppm, and a mass percentage of boron B1 is 300 ppm), conductive carbon black, polyvinylidene fluoride, and aluminum titanium phosphate in a mass ratio of 95.0:3.0:1.5:0.5 to obtain a first positive electrode active material layer slurry;

[0114] S2, a second lithium iron phosphate compound (a molar ratio of lithium to phosphorus P2 is 1.045, a mass percentage of titanium Ti2 is 1600 ppm, and a mass percentage of boron B2 is 500 ppm), conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 95.0:3.5:1.5 to obtain a second positive electrode active material layer slurry;

[0115] S3, coating the first positive electrode active material layer slurry on both sides of the positive electrode current collector aluminum foil to obtain a first positive electrode active material layer with a single-side thickness of 30 μm, then coating the second positive electrode active material layer slurry on the surface of the first positive electrode active material layer to obtain a second positive electrode active material layer with a single-side thickness of 30 μm; then drying, rolling, slitting and cutting to obtain a positive electrode sheet;

[0116] (2) Preparation of negative electrode sheet

[0117] Artificial graphite, conductive carbon black (SP), binder (sodium carboxymethyl cellulose) and styrene-butadiene rubber are mixed evenly in a mass ratio of 97:0.5:1.2:1.3, and then water is added to the above mixture in batches and continued to be fully mixed and stirred to prepare negative electrode slurry, and then the homogeneous negative electrode slurry is evenly coated on both sides of a 6μm copper foil, and after drying, rolling, slitting and cutting, a negative electrode sheet is obtained;

[0118] (3) Preparation of electrolyte

[0119] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), ethyl propionate (EP), vinylene carbonate (VC), 1,3-propane sultone (PS), vinyl sulfate (DTD), tris(trimethylsilyl) phosphate (TMSP) are mixed in a mass ratio of 20:30:45:3:1:0.5:0.5, and then lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI are added; wherein the molar concentration of LiPF6 in the electrolyte is 0.5M, and the molar concentration of LiFSI is 0.7M; the viscosity of the electrolyte at 25°C is 2.5mPa.S;

[0120] (4) Preparation of secondary batteries

[0121] The prepared positive electrode sheet, negative electrode sheet, separator and other battery components are assembled, and a secondary battery is obtained through processes such as shaping, baking, packaging, liquid injection, formation, and capacity division.

[0122] Embodiments 2 to 4

[0123] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the molar ratio of lithium element to phosphorus element is changed by adjusting the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0124] Embodiments 5 to 8

[0125] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the mass percentage of the titanium element is changed by adjusting the addition of the titanium element in the first element of the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0126] Examples 9 to 11

[0127] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the mass percentage of the boron element is changed by adjusting the addition of the boron element in the first element of the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0128] Embodiments 12 to 13

[0129] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the parameters in Tables 1 to 2 are achieved by adjusting the first element types of the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0130] Embodiments 14 to 17

[0131] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the parameters in Tables 1 to 2 are achieved by adjusting the amount of aluminum titanium phosphate added in the first positive electrode active material layer.

[0132] Embodiments 18 to 19

[0133] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the parameters in Tables 1 to 2 are achieved by adjusting the coating thickness of the first positive electrode active material layer and the second positive electrode active material layer.

[0134] Embodiment 20

[0135] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the parameters in Tables 1 to 2 are achieved by adjusting the electrolyte.

[0136] Comparative Example 1

[0137] The comparative example of the present application provides a secondary battery, which is different from Example 1 in that the molar ratio of lithium element to phosphorus element is changed by adjusting the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0138] Comparative Examples 2-3

[0139] The comparative example of the present application provides a secondary battery, which is different from Example 1 in that the parameters in Tables 1 to 2 are achieved by adjusting the addition of the first element in the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0140] Comparative Example 4

[0141] The comparative example of the present application provides a secondary battery, which is different from Example 1 in that the parameters in Tables 1 to 2 are achieved by adjusting the amount of aluminum titanium phosphate added in the first positive electrode active material layer.

[0142] Comparative Example 5

[0143] The comparative example of the present application provides a secondary battery, which is different from the embodiment 1 in that the parameters in Tables 1 to 2 are achieved by adjusting the electrolyte.

[0144] The molar ratio of lithium to phosphorus in the first positive electrode active material layer P1 and the molar ratio of lithium to phosphorus in the second positive electrode active material layer P2, as well as the difference between the two P2-P1, the mass percentage of titanium in the first lithium iron phosphate compound Ti1 / ppm and the mass percentage of titanium in the second lithium iron phosphate compound Ti2 / ppm and the difference between the two Ti2-Ti1, the mass percentage of boron in the first lithium iron phosphate compound B1 / ppm and the mass percentage of boron in the second lithium iron phosphate compound B2 / ppm and the difference between the two B2-B1 in the embodiments and comparative examples , the difference W2-W1 between the mass percentage W2 / ppm of the first element in the second lithium iron phosphate compound and the mass percentage W1 / ppm of the first element in the first lithium iron phosphate compound, the thickness expansion rate Y1 / %, the thickness expansion rate Y2 / %, of the second positive electrode active material layer, the mass percentage Z / %, of aluminum titanium phosphate in the first positive electrode active material layer, the viscosity of the electrolyte at 25°C M / mPa.s, the single-side thickness d1 / μm of the first positive electrode active material layer, and the thickness d2 / μm of the second positive electrode active material layer are as shown in Tables 1-2;

[0145] Table 1 Secondary battery parameters

[0146] P1 P2 P2-P1 Ti1 Ti2 Ti2-Ti1 B1 B2 B2-B1 W2-W1 Z Example 1 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.5 Example 2 1 1.01 0.01 1000 1600 600 300 500 200 800 0.5 Example 3 1.05 1.11 0.06 1000 1600 600 300 500 200 800 0.5 Example 4 0.98 1.21 0.23 1000 1600 600 300 500 200 800 0.5 Example 5 1.02 1.045 0.025 200 600 400 300 500 200 600 0.5 Example 6 1.02 1.045 0.025 3000 4300 1300 300 500 200 1500 0.5 Example 7 1.02 1.045 0.025 5000 6000 1000 300 500 200 1200 0.5 Example 8 1.02 1.045 0.025 5500 6500 1000 300 500 200 1200 0.5 Example 9 1.02 1.045 0.025 1000 1600 600 100 200 100 700 0.5 Example 10 1.02 1.045 0.025 1000 1600 600 1000 1500 500 1100 0.5 Embodiment 11 1.02 1.045 0.025 1000 1600 600 80 180 100 700 0.5 Example 12 1.02 1.045 0.025 0 0 0 1300 2100 800 800 0.5 Embodiment 13 1.02 1.045 0.025 1300 2100 800 0 0 0 800 0.5 Embodiment 14 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.2 Embodiment 15 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.1 Example 16 1.02 1.045 0.025 1000 1600 600 300 500 200 800 1 Embodiment 17 1.02 1.045 0.025 1000 1600 600 300 500 200 800 4 Embodiment 18 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.5 Embodiment 19 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.5 Embodiment 20 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.5 Comparative Example 1 1.045 1.02 -0.025 1000 1600 600 300 500 200 800 0.5 Comparative Example 2 1.02 1.045 0.025 1600 1000 -600 300 500 200 -400 0.5 Comparative Example 3 1.02 1.045 0.025 0 0 0 0 0 0 0 0.5 Comparative Example 4 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0 Comparative Example 5 1.02 1.045 0.025 1000 1600 600 300 500 200 800 0.5

[0147] Table 2 Secondary battery parameters

[0148] d1 d2 Y1 Y2 M Example 1 30 30 3.5 3.8 2.5 Example 2 30 30 3.6 4.3 2.5 Example 3 30 30 3.8 4.4 2.5 Example 4 30 30 4.3 4.6 2.5 Example 5 30 30 3.8 4 2.5 Example 6 30 30 3.6 4.4 2.5 Example 7 30 30 3.7 4.4 2.5 Example 8 30 30 3.8 4.6 2.5 Example 9 30 30 3.6 4.1 2.5 Example 10 30 30 3.6 3.9 2.5 Embodiment 11 30 30 3.6 4.9 2.5 Example 12 30 30 3.8 5.3 2.5 Embodiment 13 30 30 3.9 5.1 2.5 Embodiment 14 30 30 3.7 3.7 2.5 Embodiment 15 30 30 3.8 3.8 2.5 Example 16 30 30 3.9 3.9 2.5 Embodiment 17 30 30 3.8 3.6 2.5 Embodiment 18 10 60 3.4 3.4 2.5 Embodiment 19 60 10 3.8 4.1 2.5 Embodiment 20 30 30 3.4 4.1 1.5 Comparative Example 1 30 30 4.5 5.8 2.5 Comparative Example 2 30 30 4.4 5.8 2.5 Comparative Example 3 30 30 4.6 8.3 2.5 Comparative Example 4 30 30 4.5 6.1 2.5 Comparative Example 5 30 30 4.8 8.5 3.5

[0149] The energy density and storage performance of the secondary batteries prepared in the examples and comparative examples are shown in Table 3; wherein the test method comprises the following steps:

[0150] 1) Energy density: 25℃±5℃, 1C discharge to 2.0V, then 1C charge to 3.6V, cut-off current 0.05C, 1C discharge to 2.0V test capacity, 1C=4.4A; discharge platform 3.2V, energy density=capacity*discharge platform / battery length / battery width / battery thickness;

[0151] 2) Storage performance: 60℃ 100% SOC storage, 25℃±5℃, 1C discharge to 2.0V, then 1C charge to 3.6V, cut-off current 0.05C, 1C discharge to 2.0V test capacity, 1C=4.4A; record battery capacity retention rate and thickness expansion rate every 30 days;

[0152] Table 3 Secondary battery performance data

[0153]

[0154]

[0155] It can be seen from Table 3 that the technical solution provided by the present application has a high energy density and excellent storage performance; specifically, the energy density of the obtained secondary battery is above 212.6Wh / L, the capacity retention rate of 300 days, 360 days, and 400 days is above 83.4%, above 80.1%, and above 77.8%, respectively, and the thickness expansion rate of 300 days, 360 days, and 400 days is below 6.8%, below 7.5%, and below 9.2%, respectively;

[0156] The results of Examples 1 to 20 of the present application and Comparative Example 1 show that when the molar ratio P1 of the lithium element to the phosphorus element in the first positive electrode active material layer is greater than the molar ratio P2 of the lithium element to the phosphorus element in the second positive electrode active material layer, the energy density of the secondary battery obtained shows a downward trend, and the capacity retention rate during storage also decreases, and the thickness expansion rate increases; the results of Examples 1 to 20 of the present application and Comparative Example 2 show that when the mass percentage W1 of the first element in the first lithium iron phosphate compound is greater than the mass percentage W2 of the first element in the second lithium iron phosphate compound, the energy density of the secondary battery obtained shows a downward trend, and The capacity retention rate during storage also decreases, and the thickness expansion rate increases; the results of Examples 1 to 20 of the present application and Comparative Example 3 show that when the first element is not added to the first lithium iron phosphate and the second lithium iron phosphate compounds, the storage performance of the secondary battery obtained is significantly reduced; the results of Examples 1 to 20 of the present application and Comparative Example 4 show that when aluminum titanium phosphate is not added to the first positive electrode active material layer, the comprehensive performance of the secondary battery obtained shows a certain downward trend; the results of Examples 1 to 20 of the present application and Comparative Example 4 show that when the viscosity of the electrolyte at 25°C is greater than 3.0 mPa.s, the storage performance of the secondary battery obtained is significantly reduced.

[0157] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a first positive electrode active material layer and a second positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the first positive electrode active material layer is disposed between the positive electrode current collector and the second positive electrode active material layer; The first positive electrode active material layer includes a first lithium iron phosphate compound and aluminum titanium phosphate, and the second positive electrode active material layer includes a second lithium iron phosphate compound; The first lithium iron phosphate compound and the second lithium iron phosphate each independently include a first element; The first element includes titanium and / or boron; The molar ratio P1 of lithium to phosphorus in the first positive electrode active material layer is less than the molar ratio P2 of lithium to phosphorus in the second positive electrode active material layer; The mass percentage W1 of the first element in the first lithium iron phosphate compound is less than the mass percentage W2 of the first element in the second lithium iron phosphate compound; The viscosity of the electrolyte at 25° C. is ≤3.0 mPa.s.

2. The secondary battery according to claim 1, characterized in that: In the first positive electrode active material layer, the mass percentage of the aluminum titanium phosphate is 0.2-1.0%.

3. The secondary battery according to claim 1, characterized in that: The 0.01≤P2-P1≤0.

06.

4. The secondary battery according to claim 1, characterized in that: The 500ppm≤W2-W1≤1500ppm.

5. The secondary battery according to claim 1, characterized in that: The first element includes titanium and boron; The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is less than the mass percentage Ti2 of titanium in the second lithium iron phosphate compound; The mass percentage B1 of boron in the first lithium iron phosphate compound is less than the mass percentage B2 of boron in the second lithium iron phosphate compound.

6. The secondary battery according to claim 5, characterized in that: The 400ppm≤Ti2-Ti1≤1000ppm; And / or, the 100ppm≤B2-B1≤500ppm.

7. The secondary battery according to claim 5, characterized in that: At least one of the following is met: (1) The molar ratio P1 of lithium element to phosphorus element in the first positive electrode active material layer is 1.00 to 1.05; (2) the molar ratio P2 of lithium element to phosphorus element in the second positive electrode active material layer is 1.01 to 1.11; (3) The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is 200 to 5000 ppm; (4) The mass percentage of titanium Ti2 in the second lithium iron phosphate compound is 600 to 6000 ppm; (5) The mass percentage B1 of boron in the first lithium iron phosphate compound is 100 to 1000 ppm; (6) The mass percentage B2 of boron in the second lithium iron phosphate compound is 200 to 1500 ppm.

8. The secondary battery according to claim 1, characterized in that: The single-side thickness of the first positive electrode active material layer is 10 to 60 μm; And / or, the second positive electrode active material layer has a thickness of 10 to 60 μm.

9. The secondary battery according to claim 1, characterized in that: The thickness expansion rate of the first positive electrode active material layer is 3.4% to 4.3%; And / or, the thickness expansion rate of the second positive electrode active material layer is 3.4% to 5.4%.

10. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery

    CN118763284A

  • Photoconductive transcription method using sacrificial layer

    KR1020200108658A

  • Lithium-ion battery

    WO2023124831A1

  • Secondary battery and electric device comprising same

    WO2024174167A1

Cited By

  • Battery cell, battery device, and electric device

    CN122393288A